Sustainable packaging: Consumers’ evaluation of eco-labels in the Ghana’s packaging sector - Inusah Hamidu (Sustinere: Journal of Environment and Sustainability)
Fostering environmentally conscious consumer behaviour requires a clear understanding of eco-labels and sustainable packaging. However, there is a lack of research on how consumers in developing countries, especially Ghana, perceive these ideas. The study intends to address that gap by evaluating how customer perceptions of eco-friendly packaging and eco-labels are influenced by gender, age, and educational attainment. The contribute to the ongoing discourse on the predictors of environmental attitudes and behaviours. Data were collected through a cross-sectional survey with systematic sampling. Results showed that environmental perceptions were not significantly influenced by gender, age, or educational attainment. Although respondents demonstrated awareness of sustainable packaging, they had limited understanding of eco-labels, with 61% unable to correctly identify various eco-labels. The findings suggest that marketing strategies for eco-friendly products should consider factors beyond demographic characteristics. The complex interaction among demographic variables calls for a more nuanced approach to engaging consumers in sustainability initiatives. Further research is needed to explore alternative predictors of environmental attitudes and to design educational interventions that resonate with diverse consumer segments. A deeper understanding of what drive pro-environmental behaviour is essential to reduce packaging waste.